Angelina Grimke : rhetoric, identity, and the radical imagination - Browne, Stephen H. (Rhetoric and public affairs series., 1999)
Abolitionist, women's rights activist, and social reformer, Angelina Grimké (1805-79) was among the first women in American history to seize the public stage in pursuit of radical social reform. ""I will lift up my voice like a trumpet, "" she proclaimed, ""and show this people their transgressions."" And when she did lift her voice in public, on behalf of the public, she found that, in creating herself, she might transform the world. In the process, Grimké crossed the wires of race, gender, and power, and produced explosions that lit up the world of antebellum reform